The informal sector in the Mexican economy: a key factor in fostering economic development post covid 19 - Pérez - Pérez, Isabel (Universidad Francisco de Paula Santander, 2022)
In Mexico, the COVID 19 pandemic had a significant impact on the economy in the center, north and south of the country. In the south, being the poorest area, with the greatest educational backwardness and low employment, employment increased even more, worsened by the total stoppage of commercial activities in the sale of food in fixed and itinerant establishments by Presidential Decree and by the sanitary health emergency. Therefore, our objective was to analyze the economy of the informal sector in established businesses in Tonalá, Chiapas, identifying causes, consequences and proposals for possible solutions for its reactivation. A qualitative and quantitative-descriptive research was carried out, designing a semi-structured survey, which was applied to a representative sample of 50 owners/proprietors; following all safety and sanitary protocols.